2019
DOI: 10.1016/j.heliyon.2019.e02645
|View full text |Cite
|
Sign up to set email alerts
|

Study of the toxic effect and safety of vitamin E supplement in male albino rats after 30 days of repeated treatment

Abstract: The aim of these investigations was to study vitamin E supplement effect in male albino rats after 30 days of repeated treatment. Four groups of six male rats were orally administered distilled water (control), 500, 1000 and 2000 mg/kg body weight vitamin E daily for 30 days. The impact of the treatment on percent body weight and mortality was determined and compared to the control group. Some hematological analysis, biochemical parameters and histological examination of different body organs were assessed. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 55 publications
1
11
0
Order By: Relevance
“…This study is in disagreement with the work of Akinloye et al [13] which reported increased white cell count. The lack of discrepancy in the white cell count and differentials (neutrophils and lymphocyte) is an evidence of null alteration of the immune system with no inflammatory trigger to bring about a visible reaction as noted in other studies [14][15][16].…”
Section: Discussionsupporting
confidence: 56%
“…This study is in disagreement with the work of Akinloye et al [13] which reported increased white cell count. The lack of discrepancy in the white cell count and differentials (neutrophils and lymphocyte) is an evidence of null alteration of the immune system with no inflammatory trigger to bring about a visible reaction as noted in other studies [14][15][16].…”
Section: Discussionsupporting
confidence: 56%
“…The inhibition of the protective activity of GST-π could be the cause of tumour-promoting effect of vitamin E in mice ( Mitchel and McCann, 1993 ). El-Hak et al (2019) studied the effects of vitamin E supplements (daily 500, 1,000, and 2,000 mg vitamin E/kg body weight) in male albino rats. Treatment with higher doses of vitamin E caused significant changes in haematology, biochemistry and histological damage, including the kidneys.…”
Section: Adverse Effects Of Vitamin E On the Kidneys In Rodent Studiesmentioning
confidence: 99%
“…When the rats were treated with different doses of vitamin E over a period of 30 days, their kidneys and livers were affected, but proved it has no adverse effect on the testes. As such, El-Hak et al ( 36 ) recommended exercising caution when taking high doses of vitamin E. Biological and histological modifications that appear due to exposure of mice to CPF (chlorpyrifos) during gestation and lactation were reversed by an oral supplementation of vitamin E, either to the dams or to their pups ( 37 ).…”
Section: Fat-soluble Vitamins E and Kmentioning
confidence: 99%